2019
DOI: 10.1177/1060028019830785
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chemotherapy-Induced Neutropenia on Overall Survival in Patients With Unresectable or Metastatic Urothelial Carcinoma to Gemcitabine Plus Cisplatin Combination Chemotherapy

Abstract: Background: Chemotherapy-induced neutropenia (CIN) is an important dose-limiting toxicity of chemotherapy. However, evidence suggests that the occurrence of CIN may be predictive of treatment outcome. Indeed, studies have revealed that the onset of CIN is associated with a good chemotherapeutic response. Objective: The purpose of this study was to investigate the association between the onset of CIN and overall survival in patients with unresectable or metastatic urothelial carcinoma (UC) who received a combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…[3][4][5] Chemotherapy-induced neutropenia (CIN) is a signi cant dose-limiting toxicity for many cytotoxic anticancer drugs, but an interesting association between the occurrence of CIN and a favorable clinical outcome has been reported in several solid tumors. [6][7][8][9][10] In lung cancer, post-hoc analyses of clinical trials for non-small cell lung cancer have also reported that the occurrence of CIN contributes signi cantly to prolonged survival. [11] , [12] However, because of the limited number of SCLC cases, few studies have been conducted thus far to evaluate the prognostic role of CIN in patients with ED-SCLC.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Chemotherapy-induced neutropenia (CIN) is a signi cant dose-limiting toxicity for many cytotoxic anticancer drugs, but an interesting association between the occurrence of CIN and a favorable clinical outcome has been reported in several solid tumors. [6][7][8][9][10] In lung cancer, post-hoc analyses of clinical trials for non-small cell lung cancer have also reported that the occurrence of CIN contributes signi cantly to prolonged survival. [11] , [12] However, because of the limited number of SCLC cases, few studies have been conducted thus far to evaluate the prognostic role of CIN in patients with ED-SCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy-induced neutropenia is an important dose-limiting toxicity of anticancer agents, and an association between chemotherapy-induced neutropenia and good clinical response has been reported in several solid tumor types [8][9][10][11][12][13][14]. It has also been reported that the occurrence of neoadjuvant chemotherapy-induced severe neutropenia is correlated with a high histological response in patients with esophageal squamous cell carcinoma [15].…”
Section: Introductionmentioning
confidence: 99%